Integration of Ethnic Minorities: Do They Divorce as Natives Do? - Marie Louise Schultz-Nielsen; Jens Bonke (Institute for the Study of Labor (IZA), 2016)
We investigate the divorce patterns among non-Western immigrants and natives in Denmark. We focus on marriages entered on or after arrival to Denmark and analyze whether inter-ethnic marriages result in higher divorce rates and whether divorce behavior differs between first- and second-generation immigrants and native couples. We show that inter-ethnic couples (one native, one immigrant) in general are more likely to divorce than native couples (two natives), while co-ethnic couples (two immigrants) are less likely to divorce, when controlling for differences in socioeconomic characteristics. In particular, co-ethnic couples composed of a first- and second-generation immigrant are less likely to divorce, while the divorce probability is the highest among inter-ethnic couples composed of a native woman and a first-generation immigrant man. The analyses are based on register information from Statistics Denmark for the years 1990–2014.
Keywords: J12; J15; D13; 330; inter- and co-ethnic marriage and divorce